Slowing-down and stopped charged particles cause angular dependence for absorbed dose measurements - Bahadori, Amir A.; Pal Chowdhury, Rajarshi; Kroupa, Martin; Campbell-Ricketts, Thomas; Firan, Ana; Fry, Dan J.; Gaza, Ramona; George, Stuart P.; Pinsky, Lawrence S.; Stoffle, Nicholas N.; Rios, Ryan R.; Zeitlin, Cary J. (My University, 2018)
The space radiation environment is dominated by heavy charged particles with atomic numbers ranging from 1 to 93, with broad energy spectra that exceed 10 GeV per nucleon. Despite advances in space radiation modeling and transport, radiation detectors continue to provide critical data for understanding risks of health effects to astronauts in space. In the past, NASA relied on tissue-equivalent proportional counters and passive devices for operational dosimetry; however, in recent years, pixel detectors providing detailed information about the radiation environment through analysis of charged particle tracks have been demonstrated in space. These next-generation detectors, based on Timepix read-out technology, require special analysis considerations that were not necessary or possible for previous dosimetry tools. The impacts of slowing-down and stopped ions on absorbed dose measurements must be explicitly modeled to understand variations with detector orientation. The purpose of the present study is to conclusively demonstrate that while absorbed dose measurements of penetrating charged particles are independent of detector orientation, slowing-down and stopped particles can result in charged particle absorbed dose measurements that are dependent on detector orientation. Monte Carlo simulations of an unshielded detector, irradiated at selected orientations by different kinetic energy domains with fluence spectra representative of two historical solar particle events, are presented to demonstrate the dependence of absorbed dose measurements. Next, results from Monte Carlo simulations of the same energy domains and fluence spectra, isotropically impinging on an anisotropic shield configuration about the detector, are shown, to exhibit the potential for observing varying absorbed doses under realistic environment and shielding conditions. Finally, slowing-down and stopped proton data acquired with Timepix-based detectors at the Tandem Van de Graaff at Brookhaven National Laboratory are used to demonstrate the effect via accelerator-based measurements.
Citation: Bahadori, Amir A., Rajarshi Pal Chowdhury, Martin Kroupa, et al. (2018) Slowing-down and Stopped Charged Particles Cause Angular Dependence for Absorbed Dose Measurements. Radiation Physics and Chemistry. https://doi.org/10.1016/j.radphyschem.2018.06.012
Keywords: Space radiation; Timepix; Dosimetry; Solar particle event; Protons; Monte Carlo